Ammonium vanadate positive electrode material and preparation method and application thereof
By preparing a composite material in which sheet-like ammonium vanadate is uniformly grown on vapor-grown carbon fibers, the problem of poor cycle performance of vanadium-based materials is solved, and the electrochemical performance of aqueous zinc-ion batteries is improved.
Patent Information
- Application Number
- CN202411720904.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-28
AI Technical Summary
When vanadium-based materials are used as the positive electrode of aqueous rechargeable zinc batteries, they suffer from poor cycle performance, mainly due to the strong interaction with zinc ions and poor conductivity.
By mixing ammonium metavanadate solution with vapor-grown carbon fibers, adding cyclodextrin and anhydrous oxalic acid for hydrothermal reaction, a composite material in which sheet-like ammonium metavanadate is uniformly grown in situ on vapor-grown carbon fibers is prepared, thereby improving its electrical conductivity and electrochemical performance.
It improves the cycle stability and rate performance of ammonium vanadate cathode material, enhances the insertion and extraction capabilities of zinc ions, and improves electrochemical kinetic performance.
Smart Images

Figure CN119284950A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of positive electrode materials for aqueous zinc ion batteries, and in particular to an ammonium vanadate positive electrode material and a preparation method and application thereof. Background Art
[0002] Aqueous zinc-ion batteries have the advantages of high theoretical specific capacity, low redox potential, safety, reliability and environmental friendliness, and are a promising large-scale energy storage technology. Ammonium vanadate has become one of the important cathode materials for aqueous zinc-ion batteries due to its stable layered structure and excellent theoretical specific capacity. Although vanadium-based materials have high capacity and excellent cycle stability as the cathode of aqueous rechargeable zinc batteries, the strong interaction between vanadium-based materials and zinc ions and the poor reaction kinetics caused by their own poor conductivity result in poor cycle performance at high current density. Summary of the invention
[0003] The purpose of the present invention is to provide an ammonium vanadate positive electrode material and a preparation method and application thereof. The ammonium vanadate positive electrode material prepared by the preparation method has excellent cycle stability and rate performance.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing an ammonium vanadate positive electrode material, comprising the following steps:
[0006] After the ammonium metavanadate solution and the vapor-phase grown carbon fiber are mixed, cyclodextrin and anhydrous oxalic acid are added in sequence to carry out a hydrothermal reaction to obtain the ammonium vanadate positive electrode material.
[0007] Preferably, the concentration of the ammonium metavanadate solution is 5 to 20 g / L;
[0008] The ammonium metavanadate solution is prepared by mixing ammonium metavanadate and water and stirring the mixture in a water bath.
[0009] Preferably, the temperature of the water bath stirring is 40-70° C., the rotation speed of the water bath stirring is 1000-3000 rpm, and the time is 10-30 min.
[0010] Preferably, the concentration of the vapor-grown carbon fiber in the mixed solution obtained after the mixing is 1 to 10 g / L;
[0011] The mixing includes water bath stirring and ultrasound in sequence, the water bath stirring temperature is 40-70° C., the water bath stirring speed is 1000-3000 rpm, and the time is 10-30 min;
[0012] The power of the ultrasound is 200-400W, and the time is 10-30min.
[0013] Preferably, the concentration of cyclodextrin in the mixed solution obtained after adding the cyclodextrin is 5 to 30 g / L;
[0014] After adding the cyclodextrin, the process further comprises water bath stirring, wherein the water bath stirring temperature is 40-70° C., the rotation speed is 1000-3000 rpm, and the time is 1-2 hours.
[0015] Preferably, the concentration of anhydrous oxalic acid in the mixed solution obtained after adding the anhydrous oxalic acid is 5 to 30 g / L;
[0016] After adding the anhydrous oxalic acid, stirring in a water bath is further performed. The stirring temperature in the water bath is 40 to 70° C., the rotation speed is 1000 to 3000 rpm, and the stirring time is 15 to 35 minutes.
[0017] Preferably, the volume filling ratio of the hydrothermal reaction is 60-70%, the temperature is 120-200° C., and the time is 300-600 min.
[0018] Preferably, after the hydrothermal reaction is completed, washing, centrifugation, drying and cooling are further performed in sequence.
[0019] The present invention also provides an ammonium vanadate positive electrode material prepared by the preparation method described in the above technical solution, comprising vapor-grown carbon fibers and flaky ammonium vanadate in-situ grown on the surface of the vapor-grown carbon fibers.
[0020] The present invention also provides the use of the ammonium vanadate positive electrode material described in the above technical solution in an aqueous zinc ion battery.
[0021] The present invention provides a method for preparing an ammonium vanadate positive electrode material, comprising the following steps: after mixing an ammonium metavanadate solution and vapor-grown carbon fiber, cyclodextrin and anhydrous oxalic acid are added in sequence, and a hydrothermal reaction is performed to obtain the ammonium vanadate positive electrode material. The present invention realizes the bonding and compounding of ammonium metavanadate and vapor-grown carbon fiber by a hydrothermal method, and the hydrothermal method is beneficial to lowering the reaction temperature and saving energy, and there is no waste discharge during the entire reaction process, which is beneficial to environmental protection. The microstructure of the prepared ammonium vanadate positive electrode material is that the flaky ammonium vanadate is uniformly grown in situ on the vapor-grown carbon fiber, and the flaky ammonium vanadate provides more active sites for the deintercalation of zinc ions, so that the active material can be more fully contacted with the electrolyte, promote the embedding and removal of zinc ions, solve the problem of poor conductivity of ammonium vanadate, and thus improve the electrochemical performance of the material. The method improves the intrinsic conductivity of ammonium vanadate by compounding with vapor-grown carbon fiber, enhances its electrochemical kinetics, and then improves its cycle stability and capacity. At the same time, the preparation method of the present invention is simple, rapid and easy to control, and the prepared ammonium vanadate positive electrode material has uniform chemical composition and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD diagram of the ammonium vanadate positive electrode material and ammonium vanadate described in Example 1;
[0023] Figure 2 This is a SEM image of the ammonium vanadate positive electrode material described in Example 1;
[0024] Figure 3 This is the XRD pattern of the ammonium vanadate positive electrode material described in Example 2;
[0025] Figure 4 This is a SEM image of the ammonium vanadate positive electrode material described in Example 2;
[0026] Figure 5 The electrochemical impedance spectroscopy (EIS) diagram of the ammonium vanadate cathode material used in aqueous zinc ion batteries described in Example 1 is shown;
[0027] Figure 6 The cyclic voltammetry (CV) curve of the ammonium vanadate positive electrode material described in Example 1 for an aqueous zinc ion battery;
[0028] Figure 7 The ammonium vanadate positive electrode material described in Example 1 is used in aqueous zinc ion batteries at 5A·g -1 Cyclic performance curve at current density of;
[0029] Figure 8 The electrochemical impedance spectroscopy (EIS) diagram of the ammonium vanadate cathode material used in aqueous zinc ion batteries described in Example 2 is shown in FIG.
[0030] Fig. 9 The cyclic voltammetry (CV) curve of the ammonium vanadate positive electrode material used in an aqueous zinc ion battery described in Example 2;
[0031] Fig.10 The ammonium vanadate positive electrode material described in Example 2 is used for aqueous zinc ion batteries at 5A·g -1 Cyclic performance curves at current density. DETAILED DESCRIPTION
[0032] The present invention provides a method for preparing an ammonium vanadate positive electrode material, comprising the following steps:
[0033] After the ammonium metavanadate solution and the vapor-phase grown carbon fiber are mixed, cyclodextrin and anhydrous oxalic acid are added in sequence to carry out a hydrothermal reaction to obtain the ammonium vanadate positive electrode material.
[0034] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0035] In the present invention, the concentration of the ammonium metavanadate solution is preferably 5 to 20 g / L, more preferably 8 to 16 g / L. In the present invention, the ammonium metavanadate solution is preferably prepared by mixing ammonium metavanadate and water and stirring in a water bath. In the present invention, the water is preferably deionized water; the temperature of the water bath stirring is preferably 40 to 70°C, more preferably 50 to 60°C; the speed of the water bath stirring is preferably 1000 to 3000 rpm, more preferably 1500 to 2500 rpm; the time is preferably 10 to 30 min, more preferably 15 to 25 min. In an embodiment of the present invention, the concentration of the ammonium metavanadate solution may be 11.79 g / L or 13.1 g / L; the temperature of the water bath stirring may be 60°C, the speed of the water bath stirring may be 1000 rpm or 1200 rpm, and the time of the water bath stirring may be 20 min.
[0036] In the present invention, the concentration of the vapor-grown carbon fiber in the mixed solution obtained after the mixing is preferably 1-10g / L, more preferably 3-7g / L; the mixing preferably includes water bath stirring and ultrasound in sequence, and the temperature of the water bath stirring is preferably 40-70°C, more preferably 50-60°C; the speed of the water bath stirring is preferably 1000-3000rpm, more preferably 1500-2500rpm; the time is preferably 10-30min, more preferably 15-25min. In an embodiment of the present invention, the concentration of the vapor-grown carbon fiber in the mixed solution obtained after the mixing can be 4.4g / L; the temperature of the water bath stirring can be 60°C or 65°C, the speed of the water bath stirring can be 1200rpm, and the time of the water bath stirring can be 10min or 20min. In the present invention, the power of the ultrasound is preferably 200-400W, more preferably 250-350W; the time is preferably 10-30min, more preferably 15-25min. In an embodiment of the present invention, the power of the ultrasound may be 300W; the time of the ultrasound may be 20 minutes.
[0037] In the present invention, the concentration of cyclodextrin in the mixed solution obtained after adding the cyclodextrin is preferably 5-30g / L, more preferably 10-20g / L; the present invention does not have any special restrictions on the method of adding the cyclodextrin, and the method of adding known to those skilled in the art can be adopted. In the present invention, after adding the cyclodextrin, it is also preferably included in water bath stirring, and the temperature of the water bath stirring is preferably 40-70°C, more preferably 50-60°C; the rotation speed is preferably 1000-3000rpm, more preferably 1500-2500rpm; the time is preferably 1-2h. In an embodiment of the present invention, the concentration of cyclodextrin in the mixed solution obtained after adding the cyclodextrin can be 15g / L; the temperature of the water bath stirring can be 60°C or 65°C, the rotation speed can be 1500rpm, and the time can be 1h or 2h. In the present invention, the cyclodextrin is a surfactant that plays a role in reducing surface tension.
[0038] In the present invention, the concentration of anhydrous oxalic acid in the mixed solution obtained after adding the anhydrous oxalic acid is preferably 5-30g / L, more preferably 10-20g / L; the present invention does not have any special restrictions on the method of adding the anhydrous oxalic acid, and it can be added in a manner familiar to those skilled in the art. After adding the anhydrous oxalic acid, it is also preferably included in water bath stirring, and the temperature of the water bath stirring is preferably 40-70°C, more preferably 50-60°C; the rotation speed is preferably 1000-3000rpm, more preferably 1500-2500rpm; the time is preferably 15-35min, more preferably 20-30min. In an embodiment of the present invention, the concentration of anhydrous oxalic acid in the mixed solution obtained after adding the anhydrous oxalic acid can be 15g / L; the temperature of the water bath stirring can be 60°C or 65°C, the rotation speed can be 2000rpm, and the time can be 20min. In the present invention, the function of the anhydrous oxalic acid is to adjust the pH value of the solution.
[0039] In the present invention, the volume filling ratio of the hydrothermal reaction is preferably 60-70%, more preferably 63-66%; the temperature is preferably 120-200°C, more preferably 120°C; the time is preferably 300-600 min, more preferably 300 min. In the present invention, the hydrothermal reaction is preferably carried out in a reactor whose lining material is polytetrafluoroethylene.
[0040] After the hydrothermal reaction is completed, the present invention also preferably includes the first cooling, washing, centrifugation, drying, second cooling and grinding performed in sequence. In the present invention, the washing is preferably washing the suspension with deionized water and anhydrous ethanol alternately for 6 times, and after each washing, it is preferably centrifuged and the upper waste liquid is poured out. In the present invention, the speed of the centrifugation is preferably 3000-3500rpm, more preferably 3100-3400rpm; the time of each centrifugation is preferably 3-6min, more preferably 4-5min. In an embodiment of the present invention, the speed of the centrifugation can be 3200rpm, and the time of each centrifugation can be 5min. In the present invention, the drying is preferably vacuum drying, and the temperature of the vacuum drying is preferably 60-85℃, more preferably 65-80℃; the time of the vacuum drying is preferably 10-20h, more preferably 13-16h. In an embodiment of the present invention, the temperature of the vacuum drying can be 75℃ or 80℃, and the time can be 12h. The present invention does not have any special restrictions on the first cooling and the second cooling process, and the process well known to those skilled in the art can be used. The present invention does not have any special limitation on the grinding process, and the grinding process may be performed using a process well known to those skilled in the art.
[0041] The present invention also provides an ammonium vanadate positive electrode material prepared by the preparation method described in the above technical solution, comprising vapor-grown carbon fibers and flaky ammonium metavanadate in-situ grown on the surface of the vapor-grown carbon fibers.
[0042] In the present invention, the molar ratio of the vapor-grown carbon fiber to the flake ammonium metavanadate is preferably 1 to 10:1, more preferably 1 to 3:1. In an embodiment of the present invention, the molar ratio of the vapor-grown carbon fiber to the flake ammonium metavanadate may be 2:1.
[0043] The present invention also provides the use of the ammonium vanadate positive electrode material described in the above technical solution in an aqueous zinc ion battery. The present invention does not have any special limitation on the method of the application, and the method well known to those skilled in the art can be used.
[0044] The ammonium vanadate positive electrode material provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0045] Example 1
[0046] Dissolve 15 mmol of ammonium metavanadate (NH4VO3, 1.769 g) in 150 mL of deionized water, and stir in a water bath at 60°C for 20 min (speed of 1000 rpm) to obtain an ammonium metavanadate solution (orange, concentration of 11.79 g / L);
[0047] 0.5 g of vapor-grown carbon fiber (the concentration of vapor-grown fiber in the mixed solution is 3.33 g / L) was added to the ammonium metavanadate solution, stirred in a water bath at 60° C. for 10 min (speed of 1200 rpm), ultrasonicated for 20 min (power of 300 W), 2 mmol of cyclodextrin (the concentration of cyclodextrin in the mixed solution is 15.12 g / L) was added, stirred in a water bath at 60° C. for 1 h (speed of 1500 rpm), 25 mmol of anhydrous oxalic acid (the concentration of anhydrous oxalic acid in the mixed solution is 15 g / L) was added, and stirred in a water bath at 60° C. for 20 min (rotation speed is 1500rpm), the obtained mixed solution is placed in a hydrothermal reactor (volume filling ratio is 68%), and the hydrothermal reactor containing the mixed solution is placed in an electric heating oven, the temperature is raised from room temperature to 120°C and kept warm for 300min, and then naturally cooled to room temperature. The suspension in the hydrothermal reactor is washed alternately with deionized water and anhydrous ethanol for 6 times, and after each washing, the powder product is centrifuged by a centrifuge to obtain a powder product, which is then dried in an electric vacuum drying oven at 80°C for 12h, cooled to room temperature, and fully ground to obtain an ammonium vanadate positive electrode material (denoted as ①NH4V4O 10 @VGCF, the molar ratio of vapor grown carbon fiber and sheet-like ammonium metavanadate is 2:1);
[0048] Figure 1 is the XRD diagram of ammonium vanadate and ammonium vanadate positive electrode material, Figure 1 It can be seen that the addition of VGCF did not change the crystal structure of ammonium vanadate;
[0049] Figure 2 is a SEM image of the ammonium vanadate positive electrode material, Figure 2 It can be seen that ammonium vanadate is evenly distributed on the surface of VGCF to form a uniform ammonium vanadate positive electrode material.
[0050] Example 2
[0051] Dissolve 20 mmol of ammonium metavanadate (NH4VO3, 2.359 g) in 180 mL of deionized water, and stir in a water bath at 60°C for 20 min (speed of 1200 rpm) to obtain an ammonium metavanadate solution (orange, concentration of 13.1 g / L);
[0052] 0.8 g of vapor-grown carbon fiber (VGCF) was added to the ammonium metavanadate solution (the concentration of the vapor-grown fiber in the mixed solution was 4.4 g / L), stirred in a water bath at 65° C. for 20 min (the speed was 1200 rpm), ultrasonicated for 20 min (the power was 300 W), 2.5 mmol of cyclodextrin (the concentration of cyclodextrin in the mixed solution was 15.76 g / L) was added, stirred in a water bath at 65° C. for 2 h (the speed was 1600 rpm), 30 mmol of anhydrous oxalic acid (the concentration of anhydrous oxalic acid in the mixed solution was 15 g / L) was added, stirred in a water bath at 65° C. for 20 min (the speed was 1600 rpm), ), the obtained mixed solution was placed in a hydrothermal reactor (volume filling ratio was 65%), and the hydrothermal reactor containing the mixed solution was placed in an electric oven, the temperature was raised from room temperature to 120°C and kept warm for 300 minutes, and then naturally cooled to room temperature, the suspension in the hydrothermal reactor was washed alternately with deionized water and anhydrous ethanol for 6 times, and after each washing, the powder product was centrifuged by centrifuge (the centrifugal speed was 3300rpm, and the centrifugal time was 5 minutes each time), and then dried in a 75°C electric vacuum drying oven for 12 hours, cooled to room temperature, and fully ground to obtain ammonium vanadate positive electrode material (denoted as ②NH4V4O 10 @VGCF, the molar ratio of vapor-grown carbon fiber to sheet-like ammonium metavanadate is 2.5:1);
[0053] Figure 3 is the XRD diagram of ammonium vanadate and ammonium vanadate positive electrode material, Figure 3 It can be seen that the addition of VGCF did not change the crystal structure of ammonium vanadate;
[0054] Figure 4 is a SEM image of the ammonium vanadate positive electrode material, Figure 4 It can be seen that ammonium vanadate is evenly distributed on the surface of VGCF to form a uniform ammonium vanadate@VGCF composite material.
[0055] Test Case
[0056] The ammonium vanadate positive electrode material described in Examples 1 and 2 is used in an aqueous zinc ion battery, and the specific method is as follows:
[0057] The ammonium vanadate positive electrode material described in Examples 1 to 2 was mixed with conductive carbon and polyvinylidene fluoride in a mass ratio of 7:2:1, respectively, and N-dimethylpyrrolidine was used as a diluent. The mixture was fully ground to make it uniform. The uniformly mixed slurry was drop-coated on the surface of a stainless steel mesh foil electrode with a diameter of 10 mm, and vacuum dried at 80°C for 12 h. The ammonium vanadate positive electrode material loaded on each electrode surface was controlled to be 1-3 mg. A zinc foil with a diameter of 12 mm and a thickness of 10 μm was used as a negative electrode, and a glass fiber diaphragm was used as a diaphragm. 80 μL of zinc trifluoromethanesulfonate electrolyte was added, and a standard CR2032 battery was assembled and tested by a LAND-CT2001A battery test system. The full battery was charged and discharged in a voltage range of 0.3 to 1.6 V (current density was 5 A·g -1 );
[0058] Figure 5 The EIS diagram of the ammonium vanadate cathode material used in aqueous zinc ion batteries described in Example 1 is shown in FIG. Figure 5 It can be seen that the impedance of the battery is about 80 ohms;
[0059] Figure 6 The cyclic voltammetry (CV) curve of the ammonium vanadate positive electrode material used in aqueous zinc ion batteries described in Example 1 is shown in FIG. Figure 6 It can be seen that the two pairs of redox peaks are very obvious and the electrochemical activity is very high;
[0060] Figure 7 The ammonium vanadate and the ammonium vanadate positive electrode material described in Example 1 are used for aqueous zinc ion batteries at 5A·g -1 The cycle performance curve at the current density is given by Figure 7 It can be seen that the rate performance and cycle performance of the battery containing vapor-grown carbon fiber ammonium vanadate positive electrode material are greatly improved;
[0061] Figure 8 The EIS diagram of the ammonium vanadate cathode material used in aqueous zinc ion batteries described in Example 2 is shown in FIG. Figure 8 It can be seen that the impedance of the battery is about 80 ohms;
[0062] Fig. 9 The cyclic voltammetry (CV) curve of the ammonium vanadate cathode material used in aqueous zinc ion batteries described in Example 2 is shown in FIG. Fig. 9 It can be seen that the two pairs of redox peaks are very obvious and the electrochemical activity is very high;
[0063] Fig.10 The ammonium vanadate and the ammonium vanadate positive electrode material described in Example 2 are used in aqueous zinc ion batteries at 5A·g -1 The cycle performance curve at the current density is given by Fig.10 It can be seen that the rate performance and cycle performance of the battery containing vapor-grown carbon fiber ammonium vanadate positive electrode material are greatly improved.
[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an ammonium vanadate positive electrode material, characterized in that: The following steps are involved: After the ammonium metavanadate solution and the vapor-phase grown carbon fiber are mixed, cyclodextrin and anhydrous oxalic acid are added in sequence to carry out a hydrothermal reaction to obtain the ammonium vanadate positive electrode material.
2. The preparation method according to claim 1, characterized in that The concentration of the ammonium metavanadate solution is 5 to 20 g / L; The ammonium metavanadate solution is prepared by mixing ammonium metavanadate and water and stirring the mixture in a water bath.
3. The preparation method according to claim 2, characterized in that: The temperature of the water bath stirring is 40-70° C., the rotation speed of the water bath stirring is 1000-3000 rpm, and the time is 10-30 min.
4. The preparation method according to claim 1, characterized in that: The concentration of the vapor-grown carbon fiber in the mixed solution obtained after the mixing is 1 to 10 g / L; The mixing includes water bath stirring and ultrasound in sequence, the water bath stirring temperature is 40-70° C., the water bath stirring speed is 1000-3000 rpm, and the time is 10-30 min; The power of the ultrasound is 200-400W, and the time is 10-30min.
5. The preparation method according to claim 1, characterized in that: The concentration of cyclodextrin in the mixed solution obtained after adding the cyclodextrin is 5 to 30 g / L; After adding the cyclodextrin, the process further comprises water bath stirring, wherein the water bath stirring temperature is 40-70° C., the rotation speed is 1000-3000 rpm, and the time is 1-2 hours.
6. The preparation method according to claim 1, characterized in that: The concentration of anhydrous oxalic acid in the mixed solution obtained after adding the anhydrous oxalic acid is 5 to 30 g / L; After adding the anhydrous oxalic acid, stirring in a water bath is further performed. The stirring temperature in the water bath is 40 to 70° C., the rotation speed is 1000 to 3000 rpm, and the stirring time is 15 to 35 minutes.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The volume filling ratio of the hydrothermal reaction is 60-70%, the temperature is 120-200° C., and the time is 300-600 minutes.
8. The preparation method according to claim 7, characterized in that: After the hydrothermal reaction is completed, washing, centrifugation, drying and cooling are performed in sequence.
9. The ammonium vanadate positive electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The invention comprises vapor-grown carbon fibers and sheet-like ammonium metavanadate in-situ grown on the surface of the vapor-grown carbon fibers.
10. Use of the ammonium vanadate positive electrode material according to claim 9 in an aqueous zinc ion battery.
Citation Information
Patent Citations
Preparation method and application of ammonium vanadate nano material with ammonium ions partially removed in advance
CN115536066A
CC (at) NH4V4O10 (at) MXene composite material as well as preparation method and application thereof in zinc ion battery
CN116581237A
Preparation method and application of phenolphthalein intercalated ammonium vanadate material
CN117486258A
Preparation method of structural energy storage material based on zinc ion battery
CN118281359A
Cited By
Preparation method and application of ammonium vanadate material of magnesium ion battery
CN121627055A